1996
DOI: 10.1063/1.362467
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of shallow donors with proton fluence in n-type silicon

Abstract: Bipolar components that consist of p+n junctions have been irradiated by MeV protons at fluences ranging from 1011 to 1013 particles cm−2. Capacitance-voltage measurements have been used to investigate changes in the carrier concentration profiles. Shallow donors that can induce harmful effects in electronic devices have been studied as a function of fluence, flux, and annealing parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Fortunately, at the annealing temperatures where the formation of hydrogenrelated shallow donors occurred, carrier profiles almost coincided with each other irrespective of measurement temperatures, since the ratio of deep-trap concentration to shallow-donor concentration was reduced. The C-V measurement temperature was down to 30 K for such samples, and it was confirmed that carrier profiles were almost the same in the measurement temperature range 30 to 300 K. Furthermore, this result indicates that hydrogenrelated donors are indeed shallow donors as previously reported [3][4][5][6][7][8][9][10][11].…”
Section: Methodssupporting
confidence: 85%
See 3 more Smart Citations
“…Fortunately, at the annealing temperatures where the formation of hydrogenrelated shallow donors occurred, carrier profiles almost coincided with each other irrespective of measurement temperatures, since the ratio of deep-trap concentration to shallow-donor concentration was reduced. The C-V measurement temperature was down to 30 K for such samples, and it was confirmed that carrier profiles were almost the same in the measurement temperature range 30 to 300 K. Furthermore, this result indicates that hydrogenrelated donors are indeed shallow donors as previously reported [3][4][5][6][7][8][9][10][11].…”
Section: Methodssupporting
confidence: 85%
“…The carrier profiles are shown in figure 2 for hydrogen-implanted samples which are annealed at 300, 350, 400, 450, 500 and 550 • C. An increase in carrier concentration is observed at the annealing temperature of 300 • C with a concentration peak at the depth around the mean projected range R p = 0.86 µm of hydrogen implanted in this work whose value is revealed by the SIMS analysis as shown later in figure 3. This indicates the growth of the hydrogen-related shallow donors as reported previously [3][4][5][6]. It is noted that an increase in carrier concentration is seen in the shallower region than R p .…”
Section: Carrier Profilessupporting
confidence: 84%
See 2 more Smart Citations
“…It is well known that shallow donors are formed in CZ Si as a result of hydrogenation by implantation or with a rf source [33][34][35][36][37][38][39][40][41] followed by annealing at ϳ300°C or higher. Most of these donors are likely to be associated with H-enhanced thermal donors in CZ silicon due to the preponderance of interstitial oxygen O i .…”
Section: Conductivity In the Transferred Layersmentioning
confidence: 99%